Advances in genomics fungal genomics (Amsterdam Elsevier, 2007)
The sequencing of several fungi genomes has spurred major advances in the field. Fungal genomics has been having a pivotal impact on applied research in agriculture, food sciences, natural resource management, pharmaceuticals, and biotechnology, as well
Keywords: Genetics; Genomics